Review the Literary Critique of Toni Morrison Novels (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Toni Morrison, Maya Angelou, Paul Marshall, Alice Walker, and Gloria Naylor were among the American writers who saw writing as a way to break free, a strategy for rebellion, and a creative way to express oneself. She follows in Edward Said's footsteps by exploring how the dominant group manipulates black reality to serve its own agenda; Said revealed orientalism as a Western tactic for moulding and dominating the Orient. Her current projects include an Afro-centric perspective and an African-American poetics. While exploring the intricacies of black women's life in white America, she tries to comprehend the contradiction of her African-American identity. This presentation will examine Toni Morrison's works through the lens of literary criticism.